Imagine it happening to my classmates: using video testimonials as a social marketing intervention in adolescent smoking cessation programs - Mohammad Eko Fitrianto; Basu Swashta Dharmmesta; Bernardinus Maria Purwanto (Cogent Business & Management, 2024)
Each year, the average age of new smokers decreases in Indonesia, and at least one student in the classroom is a smoker. However, previous literature on adolescent smoking that focused on emotion and peer relationship remains largely underexplored. This study aimed to examine the effects of the antecedent and moderator variables of empathic concern on altruistic motivation in context of adolescent smoking prevention. We designed a school-based smoking cessation program as a social marketing intervention tool to influence high-school student behavior using a testimonial video. A simulation with a hypothetical scenario was conducted to observe students' reactions to the stimulus. Participants were exposed to a testimonial video of a young person who has suffered because of smoking, and were asked to imagine such consequences happening to their own peers. The program development started in June 2022, and was implemented in August-September 2022. A total 78 students from two experimental studies was participated. We use ANOVA to test the effect of stimuli on empathic concern and regression analysis to test the effect of empathic concern on altruistic motivation. This study found that salience of the need (light vs. severe condition) and attachment style (secure vs. Insecure) significantly affect student empathic concern. Simultaneously, empathic concern also significantly affected altruistic motivation, and no significant interaction effect was reported. In addition, the result also suggest that the affective approach is more effective in affecting empathic concern and altruistic motivation than the cognitive approach. The implications of this research suggest that schools, as organizations, can utilize a multimedia approach (e.g., video testimonials) to design comprehensive social marketing programs focused on peer relationships.
Keywords: 650; video testimonial; social marketing program; adolescent smoking; peer relationship; empathic concern; altruistic motivation